Forging Resilient Characters: SD Plus Darul Ulum's Holistic Approach to Education in a Globalized World - Zulfikar, Afifa (IAI Darussalam, 2024)
This research explores the character-building programs at SD Plus Darul Ulum, Jombang, focusing on how they cultivate resilience and toughness in students. The study delves into distinctive programs, including the Pioneering International Primary School,